Factors Associated With Postoperative Confusion and Prolonged Hospital Stay Following Deep Brain Stimulation Surgery for Parkinson Disease. Issue 4 (20th August 2019) - Abboud, Hesham; Genc, Gencer; Saad, Saira; Thompson, Nicolas; Oravivattanakul, Srivadee; Alsallom, Faisal; Yu, Xin Xin; Floden, Darlene; Gostkowski, Michal; Ahmed, Anwar; Ezzeldin, Ayman; Marouf, Hazem M; et al.
Abstract: BACKGROUND: Several patient and disease characteristics are thought to influence DBS outcomes; however, most previous studies have focused on long-term outcomes with only a few addressing immediate postoperative course. OBJECTIVE: To evaluate predictors of immediate outcomes (postoperative confusion and length of postoperative hospitalization) following deep brain stimulation surgery (DBS) in Parkinson disease (PD) patients. METHODS: We conducted a retrospective study of PD patients who underwent DBS at our institution from 2006 to 2011. We computed the proportion of patients with postoperative confusion and those with postoperative hospitalization longer than 2 d. To look for associations, Fisher's exact tests were used for categorical predictors and logistic regression for continuous predictors. RESULTS: We identified 130 patients [71% male, mean age: 63 ± 9.1, mean PD duration: 10.7 ± 5.1]. There were 7 cases of postoperative confusion and 19 of prolonged postoperative hospitalization. Of the 48 patients with tremors, none had postoperative confusion, whereas 10.1% of patients without tremors had confusion ( P  = .0425). Also, 10.2% of patients with preoperative falls/balance-dysfunction had postoperative confusion, whereas only 1.6% of patients without falls/balance-dysfunction had postoperative confusion ( P  = .0575). For every one-unit increase in score on the preoperative on-UPDRS III/MDS-UPDRS III score, the odds of having postoperative confusion increased by 10% ( P  = .0420). The following factors were noninfluential: age, disease duration, dyskinesia, gait freezing, preoperative levodopa-equivalent dose, number of intraoperative microelectrode passes, and laterality/side of surgery. CONCLUSION: Absence of tremors and higher preoperative UPDRS III predicted postoperative confusion after DBS in PD patients. Clinicians' awareness of these predictors can guide their decision making regarding patient selection and surgical planning. Graphical Abstract: